New Voter Tendency in the 15th General Election - Ismail, Mohd Mahadee; Adnan, Zatul Himmah; Ishak, Mohd Sobhi (Penerbit Universiti Kebangsaan Malaysia (UKM Press), 2023)
This paper discusses the tendency of new voters to vote for the first time in the 15th General Election (GE15). Based on the statistics released by the Election Commission (SPR), the number of new voters who voted for the first time is around 6.2 million, of which 1.3 million are between 18 and 20 years old. Since they are a group of first-time voters, the tendency of their political support could be unclearer. Many parties wonder where their political support is headed, especially in the many-cornered competition involving extensive political cooperation such as Perikatan Nasional, Pakatan Harapan, Barisan Nasional, and Gerakan Tanah Air. Accordingly, this paper aims to examine the tendency of new voters during the last GE15 campaign period through an online survey. The survey was conducted openly with the target of eligible voters, and 1438 respondents have given feedback. The study results show that 91 percent of the total number of respondents will go out to vote, and they tend to choose elected representatives who have integrity and are free of corruption, do not break promises, and are highly educated. Most of the group of respondents also tend to support national political trends. From that, new voters who vote for the first time have a good intensity of political literacy. Therefore, they become the determinants of changes in the current political support unrelated to political patronage elements like previous generations. They can also be catalysts for change in society in general and the country’s leadership in particular.